Efficient Light‐Driven Water Oxidation Catalysis by Dinuclear Ruthenium Complexes. Issue 21 (1st October 2015) - Berardi, Serena; Francàs, Laia; Neudeck, Sven; Maji, Somnath; Benet‐Buchholz, Jordi; Meyer, Franc; Llobet, Antoni
Abstract: Mastering the light‐induced four‐electron oxidation of water to molecular oxygen is a key step towards the achievement of overall water splitting to produce alternative solar fuels. In this work, we report two rugged molecular pyrazolate‐based diruthenium complexes that efficiently catalyze visible‐light‐driven water oxidation. These complexes were fully characterized both in the solid state (by X‐ray diffraction analysis) and in solution (spectroscopically and electrochemically). Benchmark performances for homogeneous oxygen production have been obtained for both catalysts in the presence of a photosensitizer and a sacrificial electron acceptor at pH 7, and a turnover frequency of up to 11.1 s −1 and a turnover number of 5300 were obtained after three successive catalytic runs. Under the same experimental conditions with the same setup, the pyrazolate‐based diruthenium complexes outperform other well‐known water oxidation catalysts owing to both electrochemical and mechanistic aspects. Abstract : Limelight on water oxidation : Two rugged pyrazolate‐based diruthenium complexes efficiently catalyze the homogeneous photoinduced water oxidation in a three‐component system including a photosensitizer and a sacrificial electron acceptor at pH 7. Outstanding results are obtained in terms of both turnover number (TON) and turnover frequency (TOF).